Gelatin-Coated TiO2/Pd Hybrid: A Potentially Useful Nanomaterial to Enhance Antibacterial and Anticancer Properties - Anbu, Periasamy; Rethinasabapathy, Muruganantham; Sathiyaseelan, Anbazhagan; Zhang, Xin; Wang, Myeong-Hyeon; Vijayakumar, Sekar; Huh, Yun Suk (International journal of molecular sciences, 2024)
Hybrid nanomaterials have attracted considerable interest in biomedicine because of their fascinating characteristics and wide range of applications in targeted drug delivery, antibacterial activity, and cancer treatment. This study developed a gelatin-coated Titanium oxide/palladium (TiO2/Pd) hybrid nanomaterial to enhance the antibacterial and anticancer capabilities. Morphological and structural analyses were conducted to characterize the synthesized hybrid nanomaterial. The surface texture of the hybrid nanomaterials was examined by high-resolution transmission electron microscopy (HR-TEM) and field-emission scanning electron microscopy (FE-SEM). The FE-SEM image revealed the bulk of the spherically shaped particles and the aggregated tiny granules. Energy dispersive X-ray spectroscopy (EDS) revealed Ti, Pd, C, and O. X-ray diffraction (XRD) revealed the gelatin-coated TiO2/Pd to be in the anatase form. Fourier transform infrared spectroscopy examined the interactions among the gelatin-coated TiO2/Pd nanoparticles. The gelatin-coated TiO2/Pd nanomaterials exhibited high antibacterial activity against Escherichia coli (22 mm) and Bacillus subtilis (17 mm) compared to individual nanoparticles, confirming the synergistic effect. More importantly, the gelatin-coated TiO2/Pd hybrid nanomaterial exhibited remarkable cytotoxic effects on A549 lung cancer cells which shows a linear increase with the concentration of the nanomaterial. The hybrid nanomaterials displayed higher toxicity to cancer cells than the nanoparticles alone. Furthermore, the cytotoxic activity against human cancer cells was verified by the generation of reactive oxygen species and nuclear damage. Therefore, gelatin-coated TiO2/Pd nanomaterials have potential uses in treating cancer and bacterial infections.